(untitled) (REMUNOM, 2026)
HSLA S700MC and AHSS S900MC steels have been increasingly used to substitute conventional steels, and further understanding of mechanical behaviors is needed. This study aims to evaluate mathematical equations for calculating the True Strain in the outer fibers of the bending zone, Springback and Bending Force that occur in the Air Bending process for these two steels, using the analytic methods of calculation and computer simulation, comparing them to the results obtained by means of experimental analysis. Four punches were used, varying the distance between the die supports and the displacement of the punch for each one of them. Experimental analysis revealed different True Strain values in the outer fibers of the bending zone. However, despite the materials having distinct mechanical properties, the values obtained through analytical calculation methods were found to be the same for both steels. While the predictability of the Springback Factor through the analytical method varied from 0.5% to 6.5% and for Bending Force the variation was from 10.0% to 38.3%.